Behavioral Responses to Wealth Taxes: Evidence from Switzerland - Marius Brülhart; Jonathan Gruber; Matthias Krapf; Kurt Schmidheiny (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study how reported wealth responds to changes in wealth tax rates. Exploiting rich intra-national variation in Switzerland, the country with the highest revenue share of annual wealth taxation in the OECD, we find that a 1 percentage point drop in the wealth tax rate raises reported wealth by at least 43% after 6 years. Administrative tax records of two cantons with quasi-randomly assigned differential tax reforms suggest that 24% of the effect arise from taxpayer mobility and 20% from house price capitalization. Savings responses appear unable to explain more than a small fraction of the remainder, suggesting sizable evasion responses in this setting with no third-party reporting of financial wealth.
Keywords: H24; H31; H73; 330; wealth taxation; behavioral responses; taxpayer mobility; evasion; Switzerland